2021
DOI: 10.1371/journal.pcbi.1008572
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling kinetic and thermodynamic models of bacterial transcription

Abstract: The study of transcription remains one of the centerpieces of modern biology with implications in settings from development to metabolism to evolution to disease. Precision measurements using a host of different techniques including fluorescence and sequencing readouts have raised the bar for what it means to quantitatively understand transcriptional regulation. In particular our understanding of the simplest genetic circuit is sufficiently refined both experimentally and theoretically that it has become possi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Previous studies have highlighted the mechanisms of multiple TF-mediated gene regulation ( Browning and Busby, 2004 ; Morrison et al, 2021 ) which consists of deterministic biochemical kinetics. Then, several mechanisms have been tested in vitro and in vivo to estimate the level of gene expression as a function of available TF concentrations ( Dodd et al, 2004 ; Bintu et al, 2005b ; Kuhlman et al, 2007 ; Garcia and Phillips, 2011 ; Garcia et al, 2012 ; Ahsendorf et al, 2014 ; Morrison et al, 2021 ). This strengthens the construction of additional mathematical models accounting for all feasible states a promoter can adopt.…”
Section: Versatility Of Gene-expression Noisementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have highlighted the mechanisms of multiple TF-mediated gene regulation ( Browning and Busby, 2004 ; Morrison et al, 2021 ) which consists of deterministic biochemical kinetics. Then, several mechanisms have been tested in vitro and in vivo to estimate the level of gene expression as a function of available TF concentrations ( Dodd et al, 2004 ; Bintu et al, 2005b ; Kuhlman et al, 2007 ; Garcia and Phillips, 2011 ; Garcia et al, 2012 ; Ahsendorf et al, 2014 ; Morrison et al, 2021 ). This strengthens the construction of additional mathematical models accounting for all feasible states a promoter can adopt.…”
Section: Versatility Of Gene-expression Noisementioning
confidence: 99%
“…Despite considerable research, the extensive roles of TFs in transcriptional dynamics remain unclear. Previous studies have highlighted the mechanisms of multiple TF-mediated gene regulation (Browning and Busby, 2004;Morrison et al, 2021) which consists of deterministic biochemical kinetics. Then, several mechanisms have been tested in vitro and in vivo to estimate the level of gene expression as a function of available TF concentrations (Dodd et al, 2004;Bintu et al, 2005b;Kuhlman et al, 2007;Garcia and Phillips, 2011;Garcia et al, 2012;Ahsendorf et al, 2014;Morrison et al, 2021).…”
Section: Promoter Architecture and Gene-expression Noise In Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the rate of protein dissociation would depend on the DNA sequence, while the association rate would be invariant with respect to sequence. Indeed, the rate of protein association with DNA has often been assumed to be sequence-independent (3)(4)(5)(6). However, single-molecule measurements have shown that when a protein scans the DNA for binding sites, the association rate does depend on the sequence (7), and that different target sequences can be bypassed with distinct probabilities (8).…”
Section: Main Textmentioning
confidence: 99%
“…4 and 5 for 1/t1,3 and 1/t3,1, which are the sought macroscopic association and dissociation rates. We then obtain (6) and , (7) where [R] is the concentration of the searching protein. We now solve for p2,3 (= ptot) in both Eq.…”
Section: Derivation Of Equation 1 and The Coupling Between Macroscopic Association And Dissociationmentioning
confidence: 99%